Statin Underprescribing for Primary Prevention of Cardiovascular Disease among Elderly Diabetic Patients in Saudi Arabia - Alshehri, Samah (Asian Journal of Pharmaceutics (AJP), 2025)
Objectives: This study aims to assess the rate of statin underprescribing among at-risk elderly diabetic patients in Saudi Arabia, as a primary prevention for cardiovascular disease. Materials and Methods: A retrospective cross-sectional data of elderly diabetic patients were obtained from the electronic database of the Academic Tertiary Center in Jeddah, Saudi Arabia. Data were retrieved from January to December 2020. Diabetic patients aged 65–79 with an atherosclerotic cardiovascular disease score of 7.5% and above were included in the study. Descriptive statistics, Chi-square test, and multivariate logistic regression were used to analyze data. P < 0.05 was considered statistically significant. Results: A total of 167 patient records were included in this study. The cohort included patients with intermediate risk (n = 121, 62.5%) and high risk (n = 46, 27.5%) of developing atherosclerotic cardiovascular disease. The rate of statin underprescribing among the study group was 52.7% (n = 88). The predictors of statin use patterns among elderly patients with diabetes and cardiovascular risk were obesity (P = 0.045) and smoking (P = 0.015). Conclusion: Over half of the study group, despite having risk factors, were not taking statin therapy. Clinicians should consider initiating statin therapy for all patients at risk of atherosclerotic cardiovascular disease while optimizing other medications to control blood pressure and glucose.